Voluntary Private Pension Funds and Capital Market Development - Togan Eğrican, Aslı; Kayhan, Fatih (Asian Academy of Management Journal of Accounting and Finance, 2022)
We examine voluntary private pension funds and their relationship to capital market development. Using data from Turkey, we analyse depth, efficiency and liquidity indicators of capital markets after the introduction of voluntary private pension funds in 2003. Overall, our findings indicate that the introduction of voluntary private pension plans are positively associated with indicators of capital market development, focusing on market depth (such as market capitalisation and trading volume) in both debt and equity markets. We also observe that indicators for other more recently established markets are also positively associated with the introduction of voluntary pension plans. In contrast, equity market turnover shows a negative association. These findings, along with the positive association with the corporate governance index, suggest that pension funds are important for capital market development and for corporate governance of firms as they are long-term investors. However, the introduction of state contributions in 2013 is not robust to alternative specifications.